Teacher Awareness And Understandings About Aboriginal English in Western Australia - Oliver, Rhonda; Rochecouste, J.; Vanderford, S.; Grote, E. (Monash University ePress, 2011)
Repeated assessments of literacy skills have shown that Aboriginal students do not achieve at the same level as their non-Aboriginal peers. Many Aboriginal students speak Aboriginal English, a dialect different from the Standard Australian English used in schools. Research shows that it is crucial for educators in bidialectal contexts to be aware of students’ home language and to adopt appropriate educational responses. For over a decade, the ABC of Two-Way Literacy and Learning Professional Development Program has sought to improve outcomes for Aboriginal students in Western Australia. By promoting a two-way bidialectal approach to learning, Aboriginal English is valued, accommodated and used to bridge to learning in Standard Australian English. This paper draws on a large research project, which used qualitative and quantitative methods to evaluate the impact of the on-going professional development for teachers. It reports on the attitudes and understandings of teachers, with and without professional development and working in different contexts.